An Alternative Way of Making Bumps for Tape Automated Bonding. (1980) - Kopejtko, Karel; Vilím, Jindřich
Abstract : Complete testing and high speed automated assembling are the main advantages which are offered by the technology called Tape Automated Bonding (TAB). The main step in this technology is a bumping of wafers which is usually performed by the IC manufacturers. When the bumped wafers are not available, the hybrid circuit manufacturers are forced to bump wafers themselves. As the bumping process consists of several operations requiring many preliminary steps, a new bumping process which is based on ultrasonic bonding of the preformed gold bumps to the aluminium pads of chips has been suggested. Compatibility of such bumped chips with TAB and the shear strength of those bumps were tested.